ANALISIS KESULITAN BELAJAR OPERASI PERKALIAN PADA SISWA SEKOLAH MENENGAH PERTAMA (SMP) - Clara Fatimah; Ketut Wirnawa; Putri Sukma Dewi (Universitas Teknokrat Indonesia, 2020)
AbstractMathematical learning can never be separated from the arithmetic operations of addition, subtraction, multiplication and division operations. Arithmetic operations that are still widely complained of by junior high school students or equivalent are multiplication arithmetic operations. This study aims to determine the location of students' difficulties in multiplication operations. The analysis technique in this article uses quantitative methods with descriptive and inferential statistical techniques. The subjects of this study were 25 junior high students in Lampung Province. Difficulties faced by students is that it is difficult to understand the intentions of the questions which reach 40%, these difficulties which trigger other difficulties arise. These difficulties include unit multiplication operations, tens, hundreds to thousands. Researchers collected data using a Google form web-based interactive service questionnaire by giving a test in the form of 10 story questions and a column of reasons for difficulty while working on the questions. The questions given refer to the level of difficulty, the validity of the questions with the Product Moment correlation technique for each item and the reliability that reaches 0.707 using the Cronbach Alpha method. Obtained 55% of junior high school students or equivalent difficulty when working on the problem.Keywords: Multiplication, Junior high school, Student difficulties.